Absolute Postoperative B-Type Natriuretic Peptide Concentrations, but Not Their General Trend, Are Associated With 12-Month, All-Cause Mortality After On-Pump Cardiac Surgery. (September 2017) - Mauermann, Eckhard; Bolliger, Daniel; Fassl, Jens; Grapow, Martin; Seeberger, Esther E.; Seeberger, Manfred D.; Filipovic, Miodrag; Lurati Buse, Giovanna A. L.
Abstract : BACKGROUND: B-type natriuretic peptide (BNP) is a predictor of mortality after on-pump cardiac surgery. However, previous limited and heterogeneous studies have focused on peak concentrations at 3 to 5 days after surgery and may not offer clinicians much help in early decision-making. After confirming the predictive value of first-postoperative-day BNP in a preliminary analysis, we explored the association between isolated second-postoperative-day BNP concentrations, second-day BNP concentrations in conjunction with first-day BNP concentrations, and the change in BNP (ie, ΔBNP) from the first to the second postoperative day and 12-month, all-cause mortality. METHODS: We included consecutive patients undergoing on-pump cardiac surgery in this observational, secondary analysis of prospectively collected data. We analyzed biomarkers on the first and second postoperative day. ΔBNP was defined as BNP on the second postoperative day minus BNP on the first postoperative day. The primary end point was 12-month, all-cause mortality. The secondary end point was a composite of major adverse cardiac events (MACEs) at 12 months and/or all-cause mortality at 12 months. MACE was defined as nonfatal cardiac arrest, myocardial infarction, and congestive heart failure. The association between BNP and outcomes was examined by receiver operating characteristic curves, as well as univariate and multivariable logistic regression, adjusting for the EuroSCORE II, cross-clamp time, and first-postoperative-day troponin T. RESULTS: We included 1199 patients in the preliminary analysis focused on BNP on postoperative day 1. In the analyses examining BNP variables requiring second-postoperative-day BNP measurement (n = 708), we observed 66 (9.3%) deaths, 48 (6.8%) MACE, and 104 (14.7%) deaths and/or MACE. Both first- and second-postoperative-day BNP were significant independent predictors of all-cause, 12-month mortality per 100 ng/L increase (adjusted odds ratio [aOR], 1.040 [95% confidence interval (CI), 1.019–1.065] and 1.064 [95% CI, 1.031–1.105], respectively). When used in conjunction with one another, first-day BNP was not significant (aOR, 1.021 [95% CI, 0.995–1.048]), while second-day BNP remained significant (aOR, 1.046 [95% CI, 1.008–1.091]). The ΔBNP per 100 ng/L increase was not associated with 12-month, all-cause mortality in the univariable (OR, 0.977 [95% CI, 0.951–1.007]) or multivariable analysis (aOR, 0.989 [95% CI, 0.962–1.021]). CONCLUSIONS: Both absolute concentrations of first- and second-postoperative-day BNP are independent predictors of 12-month, all-cause mortality. When modeled together, second-postoperative-day BNP is more predictive of 12-month, all-cause mortality. Although intuitively appealing, the change in BNP from the first to the second postoperative day is a complex variable and should not routinely be used for prognostication. Abstract : Supplemental Digital Content is available in the text.